In vitro digestion and human gut microbiota fermentation of Bletilla striata polysaccharides and oligosaccharides - Wang, Qiqi; Chen, Huimin; Yin, Mingzhu; Cheng, Xue; Xia, Hui; Hu, Haiming; Zheng, Junping; Zhang, Zhigang; Liu, Hongtao (Frontiers in Cellular and Infection Microbiology, 2023)
Bletilla striata is one of the commonly used Chinese medicinal materials. Bletilla striata polysaccharides (BP) and oligosaccharides (BO) were proved to have a variety of biological activities. However, the digestion and fermentation characteristics of BP and BO are still unclear. In this study, we evaluated their different prebiotic effects by in vitro simulating digestion and gut microbiota fermentation. The results show that the simulating saliva partly degraded BP, but had no effect on BO. The molecular weights of BP and BO remained basically unchanged in gastric and intestinal digestion. In addition, BP and BO could be rapidly degraded and utilized by gut microbiota. During in vitro fermentation, the growth rates of the BP and BO groups were higher than that of the Control group. The fermentation resulted in decreased pH levels and total carbohydrates between the BP and BO groups. Although the reducing sugar level in the BO group decreased rapidly, it remained at a low level in the BP group. Both BP and BO improved the composition and structure of gut microbiota, indicative of the upregulated abundances of Streptococcus and Veroniella, and the downregulated populations of Esherichia and Bacteroides. There were differences in the SCFA production by gut microbiota and antioxidant activities between the BP and BO groups. The fermentation broth of the BP group displayed a stronger suppression of O2-, but a higher scavenging effect on DPPH for the BO group. In summary, BP and BO displayed different digestion and fermentation characteristics in vitro due to their distinct polymerization degrees. Our studies point towards the potential of BP and BO as prebiotics in the application to human diseases by selectively regulating gut microbiota in the future.